The TMS Motor Map Does Not Change Following a Single Session of Mirror Training Either with Or without Motor Imagery - van de Ruit, Mark; Grey, Michael J. (Frontiers in Human Neuroscience, 2017)
Both motor imagery and mirror training have been used in motor rehabilitation settings to promote skill learning and plasticity. As motor imagery and mirror training are suggested to be closely linked, it was hypothesised that mirror training augmented by motor imagery would increase corticospinal excitability significantly compared to mirror training alone. Forty-four participants were split over two experimental groups. Each participant visited the laboratory once to receive either mirror training alone or mirror training augmented with layered stimulus response training, a type of motor imagery training. Participants performed 16 minutes of mirror training, making repetitive grasping movements paced by a metronome. Transcranial magnetic stimulation (TMS) mapping was performed before and after the mirror training to test for changes in corticospinal excitability of the untrained hand. Self-reports suggested that the imagery training was effective in helping the participant to perform the mirror training task as instructed. Nonetheless, neither training type resulted in a significant change of TMS map area, nor was there an interaction between the groups. The results from the study revealed no effect of a single session of 16 minutes of either mirror training or mirror training enhanced by imagery on TMS map area. Despite the negative result of the present experiment, this does not suggest that either motor imagery or mirror training might be ineffective as a rehabilitation therapy. Further study is required to allow disentangling the role of imagery and action observation in mirror training so that mirror training can be further tailored to the individual according to their abilities.